Iceland's Circularity Index - Guðmundur Steingrímsson 1972- (2022)
With a growing global population and growing consumption, the extraction of raw materials from natural resources has become unsustainable. One way to reduce the extraction of raw materials is to use materials again. Numerous nations around the world have declared that they will make their economies more circular in that way, in accordance with the principles of the circular economy. Iceland is among those nations. However, a useful measurement of how circular an economy is at any given time has been lacking. This thesis provides a comprehensive assessment of Iceland’s circularity, by use of Economy-Wide Material Flow Accounting. The assessment is done within the methodological framework of four recent national circularity reports of other European nations. This monitoring framework provides policymakers and other stakeholders with a measurement of circularity in the form of a National Circularity Index and a National Circularity Gap. According to this study, the Icelandic economy is 8,5% circular. This means that while fulfilling their needs within the economy the habitants of Iceland use secondary or cycled materials in 8,5% of all materials used. This is Iceland’s National Circularity Index. Accordingly, Iceland’s Circularity Gap is 91,5%. This makes Iceland very much a linear economy, as opposed to a circular one. Suggestions are made on how circularity can be increased, and different scenarios, including more circular consumption of biomass, fossils, and construction materials, are assessed. An analysis of this kind has not been performed before in Iceland. The information provided should be useful for future decision-making and might increase circularity. Með vaxandi fólksfjölda í heiminum og aukinni neyslu hefur nýting náttúruauðlinda orðið ósjálfbær. Ein leið til þess að minnka hráefnisöflun úr náttúrunni er að nota efni aftur, í hringrás. Fjölmörg ríki heimsins hafa lýst því yfir að þau stefni að innleiðingu hringrásarhagkerfis, Ísland þar á meðal. Mælikvarða á árangur slíkar innleiðingar hefur hins ...